Evaluation of efficacy of antioxidant‐enriched sunscreen products against long wavelength ultraviolet A1 and visible light - Ruvolo, Eduardo; Boothby‐Shoemaker, Wyatt; Kumar, Nishant; Hamzavi, Iltefat H.; Lim, Henry W.; Kohli, Indermeet (International journal of cosmetic science, 2022)
Objective The synergistic effects of VL and long wavelength UVA1 (VL + UVA1, 370–700 nm) on inducing pigmentation and erythema in skin have been demonstrated and linked to exacerbation of dermatologic conditions including melasma and post‐inflammatory hyperpigmentation. This study aimed to compare the photoprotection of organic sunscreens enriched with antioxidant (AO) combinations against VL + UVA1 induced biologic effects. The efficacy was compared with that offered by a commercially available tinted sunscreen. Methods Ten healthy adult subjects with Fitzpatrick skin phototypes IV–VI were enrolled (nine completed). VL + UVA1 dose of 380 J/cm2 was utilized. Assessment methods were polarized photography, investigator global scoring and diffuse reflectance spectroscopy (DRS). Measurements were obtained at baseline and immediately, 24 h and 7 days after irradiation. Results Sites treated with tinted sunscreen product had significantly less pigmentation compared with untreated but irradiated skin at all time points. However, DRS results demonstrated that the 5‐AO sunscreen performed comparably or better than all sunscreens tested with relatively lower dyschromia, delayed erythema and pigmentation. Conclusion These results highlight the potential of AO‐enriched sunscreens to be photoprotective against VL + UVA1. The combination of efficacy and the cosmetic appearance of this product may provide wider acceptability which is crucial considering the limited available means of protection against this waveband.